Krashen's Monitor Model in L2 Acquisition: A Critical Review - Mahmudul Hassan (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2022)
Stephen Krashen is well-known for a set of theories collectively known as the Monitor Model, which have made substantial contributions to the fields of language learning and writing. It is likely the most often quoted second language acquisition theory and has frequently dominated education discourse. Originally published around forty years ago, the Monitor Model contains a series of ideas which have evolved and are still debated today. Despite widespread criticism, the theory has had far-reaching effects on second language research and instruction since its inception. Controversies surrounding the Monitor Model propelled the discussion on what a theory of L2 acquisition ought to be. This paper evaluates Krashen's Monitor Model critically. It gives a thorough analysis of the model's underlying assumptions, explains each of the five hypotheses, and addresses objections to the theory based on relevant empirical evidence. It also evaluates some of Krashen's rebuttals to some of the objections made to his theories. The study reveals that despite the theoretical flaws, some of Krashen's fundamental assumptions appear to be valid. The research also concludes that Krashen's monitor model is still legitimate and relevant because its core concepts have survived in some form despite years of scathing criticism.